A Simple Assay to Assess Salmonella Typhimurium Impact on Performance and Immune Status of Growing Pigs after Different Inoculation Doses - Alves da Cunha Valini, Graziela [UNESP]; Arnaut, Pedro Righetti [UNESP]; Barbosa, Larissa Gonçalves [UNESP]; de Azevedo, Paulo Henrique Amadeu [UNESP]; Melo, Antonio Diego Brandão [UNESP]; Marçal, Danilo Alves [UNESP]; Campos, Paulo Henrique Reis Furtado; Hauschild, Luciano [UNESP] (MDPI, 2023)
Salmonella Typhimurium is the most frequent serovar in pigs and causes infections in humans. However, the dosage used for experimentation is not well defined. The present study aimed to evaluate a dosage for oral inoculation with Salmonella Typhimurium to assess immunological and growth performance alterations in pigs. Gilts were randomly allocated into one of three experimental treatments: no Salmonella Typhimurium inoculation (Basal), or oral inoculation of 1 × 108 or 1.5 × 108 colony-forming units of Salmonella Typhimurium. Growth rate, rectal temperature, and fecal Salmonella shedding were recorded. Blood samples were taken. Inoculated pigs shed the bacteria for up to 7 days, but no differences were observed between the groups. No differences were observed in rectal temperature, body weight, or average daily feed intake. However, reductions in average daily gain (−17 and −22%) and feed efficiency (−14 and −20%) were observed in pigs inoculated with 1 × 108 and 1.5 × 108 colony-forming units, respectively. The hemoglobin and hematocrit concentrations increased in challenged pigs compared to Basal pigs. The oral dosage of 1.5 × 108 colony-forming units of Salmonella Typhimurium is suitable for activating the immune system of pigs and assessing the impact of Salmonella on pig performance.
Keywords: growth; immunologic response; sanitary challenge; swine